Penentuan konsentrasi hambat minimum dan konsentrasi bunuh minimum ekstrak dan nanopartikel ekstrak daun pepaya (Carica Papaya L.) terhadap Bakteri Cutibacterium acnes - Khofifah , Nur; Rahayu, Yayuk Putri; Nasution , Haris Munandar; Miswanda, Dikki (Journal of Pharmaceutical and Sciences, 2025)
One of the skin diseases that often occurs is acne (Acne vulgaris). Acne is caused by the activity of the Cutibacterium acnes bacteria. Current acne treatment still depends on the use of antibiotics, but long-term use of antibiotics can cause bacterial resistance. Therefore, it is necessary to develop alternative treatments for acne that are effective and safe, one of which is by using medicinal plants. One plant that has potential is papaya leaves (Carica papaya L.). This research aims to determine the minimum inhibitory concentration (MIC) and minimum killing concentration (KBM) of ethanol extract and papaya leaf extract nanoparticles as well as testing antibacterial activity against Cutibacterium acnes bacteria. The research was carried out experimentally. The independent variables are the concentration of papaya leaf extract (6.25% concentration, 12.5% ​​concentration, 25% concentration and 50% concentration), and the concentration of papaya leaf extract nanoparticles (0.625% concentration, 1.25% concentration, 2.5% concentration % and Concentration 5%). The dependent variable is the antibacterial activity of papaya leaf ethanol extract and nanoparticles extract against Cutibacterium acnes. Characterization of the size of the extracted nanoparticles using a Particle Size Analyzer (PSA). The characteristic results for the extract size were 2,203.45 nm while the size of the extract nanoparticles was 330.27 nm. The minimum inhibitory concentration (MIC) value of 1.25% papaya leaf ethanol extract nanoparticles is better than 12.5% ​​papaya leaf ethanol extract, and the minimum lethal concentration (KBM) value of 5% papaya leaf ethanol extract nanoparticles is better than papaya leaf ethanol extract 50% against Cutibacterium acnes bacteria. 5% papaya leaf ethanol extract nanoparticles have the same antibacterial ability as 50% papaya leaf ethanol extract and are sensitive to Cutibacterium acnes bacteria, so it can be said that 5% papaya leaf ethanol extract nanoparticles can reduce the dose concentration of antibacterial compounds up to one-tenth of the time compared to ethanol extract papaya leaves 50% (1:10)